Towards closing cassava yield gap in west Africa: agronomic efficiency and storage root yield responses to NPK fertilizers - Adiele, J.G.; Schut, Antonius G.T.; Beuken, R.P.M. van den; Ezui, K.S.; Pypers, Pieter; Ano, A.O.; Egesi, Chiedozie N.; Giller, Kenneth E. (Elsevier, 2020)
Nutrient management of cassava has received little attention compared with cereal crops. We evaluated cassava yield potential and nutrient use efficiency when supplied with nitrogen, phosphorus and potassium at high rates and when supplied with increasing rates of K. On-farm experiments were conducted at six locations in Nigeria across the major cassava growing agro-ecologies of Western Africa (Tropical Rainforest – Cross River, Forest Transition Savanna – Edo, and Guinea Savanna – Benue) during two seasons (2016–2017 and 2017–2018). Nitrogen, P and K fertilizers were applied at various rates, including treatments with and without added secondary and micronutrients. Storage root dry matter (DM) yields ranged between 11 and 35 t DM ha−1. The largest yields were obtained with a mean agronomic efficiency of 60, 162 and 51 kg DM of storage roots per kg of N, P and K applied, with average uptakes of 364, 44 and 242 kg N, P and K ha−1 respectively. Storage root yield responses to applied N, P and K fertilizers (2–18, 3–16 and 3–22 t DM ha−1, respectively) varied across the locations, reflecting variability in potential yields and applied NPK ratios. Addition of a mixture of secondary and micronutrients did not affect cassava yields. We found that the caloric energy yield of cassava per kg of N applied is 2.7 times larger than the value reported for maize. Increasing the supply of K gave a high agronomic efficiency of N even when supplied at high rates, supporting the theory of “increasing returns to scale” of De Wit. We conclude that cassava has a major role in future food security of sub-Saharan Africa, with potentially larger DM yields, a better recovery of applied nutrients and larger energy yield per kg of applied N fertilizer when compared with grains.